On the complex relationship between Law and trust - Ansuátegui Roig, Francisco Javier (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article is part of the monographic section "Derecho y confianza” In this paper I analyse Tommaso Greco’s proposal regarding the relationship between Law and trust, focusing on some relevant points and showing its complex and multidimensional nature; and showing some consequences related to the concept of Law.